Keterampilan Guru Dalam Mengelola Kelas - Putri Utami; Muhammad Arif; Tivany Ramadhani; Aulia Khairani; Safran Safran (Politeknik Kampar, 2024)
One of the skills that an educator must have is class management skills. Class management is very important for the continuity of the learning process. Class management is the key to success in learning activities. This research aims to find out how teachers' skills are in managing classes in class IV of SD Negeri 060904 Medan Maimun. This research uses a qualitative approach. Data collection techniques are primary data and secondary data. Primary data sources in this research were obtained through interviews and observations. Meanwhile, secondary data sources are data obtained from library studies such as journals, reports, articles, books and the internet that are related to research. The results obtained from this research are that teacher skills in managing the classroom can be done in two ways, namely: 1) by creating and maintaining ideal or preventive learning conditions, 2) by developing and controlling optimal or repressive learning conditions.